High throughput DNA sequencing: The new sequencing revolution - Delseny, M.; Han, B.; Hsingc, Y.L.
Improvements in technology have rapidly changed the field of DNA sequencing. These improvements are boosted by bio-medical research. Plant science has benefited from this breakthrough, and a number of plant genomes are now available, new biological questions can be approached and new breeding strategies can be designed. The first part of this review aims to briefly describe the principles of the new sequencing methods, many of which are already used in plant laboratories. The second part summarizes the state of plant genome sequencing and illustrates the achievements in the last few years. Although already impressive, these results represent only the beginning of a new genomic era in plant science. Finallywedescribe some of the exciting discoveries in the structure and evolution of plant genomes made possible by genome sequencing in terms of biodiversity, genome expression and epigenetic regulations. All of these findings have already influenced plant breeding and biodiversity protection. Finallywediscuss current trends, challenges and perspectives.
Keywords: DNA SEQUENCING; PLANT GENOME; GENOME STRUCTURE AND EVOLUTION; TRANSPOSABLE ELEMENTS; EPIGENOME SEQUENCING; TRANSCRIPTOME SEQUENCING